(3GdGNJjGQ dJYdjd GdeNJGQs - (3GdehUdj, CHh GdaVd, YHO Gddg Hf eMehO Hf ehOhO, J (B683 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj TQY dfG OjfG bhjeG hHYO acfJ LeYJ aj YfahGf THGHj eNJUQG aj Gdabg hSejJg HGdeNJGQ ddaJhi adeG JOGhdJg CjOj GdYdeGA hGTJZd Hg GdabgGA WdHhG efj Cf CTQMg hTQYJ ajg eSJYjfG HGddg hSejJg GdGNJjGQ dJYdjd GdeNJGQs
(3BNQgG (B:s
(3jHbi eGFI hSJhf aEPG CNP GdSGHY SHYjf hJSY GdHGbj YTQI jHbi KeGfhf jCNPgG GdKGef abO MUd dcd hGMO efge KeGfhf hGddg CYdes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 135s
(3eYLe GdeDdajf (B2 / 295s
(3cTa GdXfhf (B2 / 1622s
(3gOjI GdYGQajf (B1 / 462s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs